2019
DOI: 10.1002/chem.201900778
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Assisted Opening of Intact P4 Tetrahedra

Abstract: The reactivity of ruthenium and manganese complexes bearing intact white phosphorus in the coordination sphere was investigated towards the low‐valent transition‐metal species [Cp′′′Co] (Cp′′′=η5‐C5H2‐1,2,4‐tBu3) and [L0M] (L0=CH[CHN(2,6‐Me2C6H3)]2; M=Fe, Co). Remarkably, and irrespective of the metal species, the reaction proceeds by the selective cleavage of two P–P edges and the formation of a square‐planar cyclo‐P4 ligand. The reaction products [{CpRu(PPh3)2}{CoCp′′′}(μ,η1:4‐P4)][CF3SO3] (5), [{CpBIGMn(CO)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 77 publications
1
7
0
Order By: Relevance
“…These bond lengths are in good agreement with the determined P-P distances in the isolated cyclo-P 4 2À anion (2.146(1) and 2.1484(9) Å) in Cs 2 P 4 Á2NH 3 24 as well as in other complexes with formal P 4 2À ligands. 16,22,25 The cyclo-P 4 units exhibit similar diamond-shaped geometries in all three complexes, which was also found in the other complexes derived from 1. During this reaction, all acetonitrile ligands are substituted by 1, while the P 4 core isomerises to a cyclic P 4 unit.…”
supporting
confidence: 60%
See 2 more Smart Citations
“…These bond lengths are in good agreement with the determined P-P distances in the isolated cyclo-P 4 2À anion (2.146(1) and 2.1484(9) Å) in Cs 2 P 4 Á2NH 3 24 as well as in other complexes with formal P 4 2À ligands. 16,22,25 The cyclo-P 4 units exhibit similar diamond-shaped geometries in all three complexes, which was also found in the other complexes derived from 1. During this reaction, all acetonitrile ligands are substituted by 1, while the P 4 core isomerises to a cyclic P 4 unit.…”
supporting
confidence: 60%
“…18 In solution it dissociates into the 14-valence-electron (VE) fragment [Cp 0 0 0 Co] and reacts readily with complexes bearing intact tetrahedral P 4 units to cyclo-P 4 (type B) containing derivatives. 16 On the other hand we showed that the formation of the butterfly complex [{Cp 0 0 0 Fe(CO) 2 } 2 (m,Z 1 : 1 -P 4 )] 9 (1) by the reaction of [Cp 0 0 0 Fe(CO) 2 ] 2 with P 4 does not need thermal activation and already occurs quantitatively at room temperature. 19 The reactivity of 1 is very versatile, since the reaction with PhCRCPh or PRC t Bu gives access to triphospholyl-and tetraphospholyl-containing iron complexes.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…[ 6 , 7 , 8 , 9 , 10 ] Further examples in which only one P−P bond is opened are the formation of the butterfly complexes [{Cp R Fe(CO) 2 } 2 (μ,η 1:1 ‐E 4 )] (Cp R =Cp′′′ (1,2,4‐tri‐ tert ‐butyl‐cyclopentadienyl), Cp BIG (pentakis‐(4‐ n ‐butyl‐phenyl)cyclopentadienyl)) and [{Cp*Cr(CO) 3 } 2 (μ,η 1:1 ‐E 4 )] (Cp*=pentamethyl‐cyclopentadienyl) by the reaction of E 4 (E=P, As) with metal carbonyl dimers. [11] By using the toluene complex [(Cp′′′Co) 2 (μ,η 4:4 ‐C 7 H 8 )], it is possible to break two P−P bonds simultaneously in E 4 either into two E 2 dumbbells to give the triple‐decker complexes [(Cp R Co) 2 (μ,η 2:2 ‐E 2 ) 2 ] (E=P, As, Cp R = Cp′′′, Cp*), [12] or compounds containing a cyclo ‐P 4 unit as end‐deck as in [(Cp′′′Co)(η 4 ‐P 4 )][ 13 , 14 ] or in [{CpRu(PPh 3 ) 2 }{CoCp′′′}‐(μ,η 1:4 ‐P 4 )][CF 3 SO 3 ] and [{Cp BIG Mn(CO) 2 } 2 {CoCp′′′}(μ,η 1:1:4 ‐P 4 }], respectively. [14] …”
Section: Introductionmentioning
confidence: 99%
“…[11] By using the toluene complex [(Cp′′′Co) 2 (μ,η 4:4 ‐C 7 H 8 )], it is possible to break two P−P bonds simultaneously in E 4 either into two E 2 dumbbells to give the triple‐decker complexes [(Cp R Co) 2 (μ,η 2:2 ‐E 2 ) 2 ] (E=P, As, Cp R = Cp′′′, Cp*), [12] or compounds containing a cyclo ‐P 4 unit as end‐deck as in [(Cp′′′Co)(η 4 ‐P 4 )][ 13 , 14 ] or in [{CpRu(PPh 3 ) 2 }{CoCp′′′}‐(μ,η 1:4 ‐P 4 )][CF 3 SO 3 ] and [{Cp BIG Mn(CO) 2 } 2 {CoCp′′′}(μ,η 1:1:4 ‐P 4 }], respectively. [14] …”
Section: Introductionmentioning
confidence: 99%